A new legacy: potential of zooarchaeology by mass spectrometry in the analysis of North American megafaunal remains - Antonosyan, Mariya; Hill, Eden; Jodry, Margaret; Amano, Noel; Brown, Samantha; Rick, Torben; Boivin, Nicole (Frontiers in Mammal Science, 2024)
Museum legacy collections, often derived from large-scale archaeological excavations, can serve as paleoenvironmental archives of Late Pleistocene megafaunal composition and dynamics. Many of these collections, however, contain large quantities of highly fragmented and morphologically indistinct bones that cannot be identified to a specific taxon and are therefore of limited use to paleoenvironmental and archaeological analyses. Here, we explore the potential of Zooarchaeology by Mass Spectrometry (ZooMS) to identify fossil bone fragments and complement morphological identifications in legacy collections housed at the Smithsonian's National Museum of Natural History. To undertake this work, we collected fragmented bone specimens of Late Pleistocene megafauna from six archaeological sites in Colorado that are currently housed in the Department of Anthropology, and then performed pilot ZooMS screening. Our analysis successfully retrieved taxonomic information from 80% of the analyzed material, highlighting the potential of future ZooMS studies on museum collections to investigate human-megafaunal interactions in late Pleistocene North America.